Tissue Distribution of ACE2 Protein in Syrian Golden Hamster (Mesocricetus auratus) and Its Possible Implications in SARS-CoV-2 Related Studies - Suresh, Voddu; Parida, Deepti; Minz, Aliva P.; Sethi, Manisha; Sahoo, Bhabani S.; Senapati, Shantibhusan (Frontiers in Pharmacology, 2021)
The Syrian golden hamster (Mesocricetus auratus) has recently been demonstrated as a clinically relevant animal model for SARS-CoV-2 infection. However, lack of knowledge about the tissue-specific expression pattern of various proteins in these animals and the unavailability of reagents like antibodies against this species hampers these models' optimal use. The major objective of our current study was to analyze the tissue-specific expression pattern of angiotensin-converting enzyme 2 (ACE2), a proven functional receptor for SARS-CoV-2 in different organs of the hamster. Using two different antibodies (MA5-32307 and AF933), we have conducted immunoblotting, immunohistochemistry, and immunofluorescence analysis to evaluate the ACE2 expression in different tissues of the hamster. Further, at the mRNA level, the expression of Ace2 in tissues was evaluated through RT-qPCR analysis. Both the antibodies detected expression of ACE2 in kidney, small intestine, tongue, and liver. Epithelium of proximal tubules of kidney and surface epithelium of ileum expresses a very high amount of this protein. Surprisingly, analysis of stained tissue sections showed no detectable expression of ACE2 in the lung or tracheal epithelial cells. Similarly, all parts of the large intestine were negative for ACE2 expression. Analysis of tissues from different age groups and sex didn’t show any obvious difference in ACE2 expression pattern or level. Together, our findings corroborate some of the earlier reports related to ACE2 expression patterns in human tissues and contradict others. We believe that this study's findings have provided evidence that demands further investigation to understand the predominant respiratory pathology of SARS-CoV-2 infection and disease.